Faecal calprotectin determination : impact of preanalytical sample treatment and stool consistency on within- and between-method variability - Juričić, Gordana (Array, 2018)
Introduction: We assessed the differences in faecal calprotectin (FC) concentrations measured by two assays depending on the stool consistencyand extraction method.Materials and methods: Stool samples were extracted using the EliA Stool Extraction Kit, Calex® Cap extraction device and respective weighingmethods, while FC concentrations were measured using the EliATM Calprotectin and Bühlmann fCAL® Turbo method and checked for within- andbetween-method variability with regard to extraction method and stool consistency category. Extraction yield was evaluated for impact of differentsample incubation time (10 min and 1 h) in extraction buffer for both methods and for impact of different initial sample dilutions (1:50, 1:100, 1:500)for fCAL® Turbo method.Results: Results determined from Calex® Cap extracts were higher compared to weighing method extracts (mean bias 33.3%; P <0.001), whileno significant difference was found between results obtained with EliA Stool Extraction Kit and weighing method (mean bias 0.1%; P = 0.484), inboth cases irrespective of stool consistency. Bühlmann fCAL® Turbo results were higher than EliATM Calprotectin results (mean bias 32.3%, P = 0.025weighing method; and mean bias 53.9%, P <0.001 extraction devices), the difference is dependent on stool consistency and FC concentration. Significantlyhigher FC extraction yield was obtained with longer sample incubation time for both methods (P = 0.019 EliATM Calprotectin; P <0.001fCAL® Turbo) and with increasing initial sample dilution for fCAL® Turbo method (P <0.001).Conclusion: Preanalytical stool sample handling proved to be a crucial factor contributing to within- and between-FC assay variability. Standardizationis urgently needed in order to assure comparable and reliable FC results.